The Formation of Nationalism Through Education of Citizenship In Elementary School - Ulfah, Nufikha; Hidayah, Yayuk; Halimah, Lili (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Character education which is intended to love the motherland is one of the character education that must be instilled for every young generation from an early age. The purpose of this study is to find out how to instill national character (nationalism) through learning Citizenship Education in Primary Schools. The method used is the study of literature (literature study) on books and learning tools for Citizenship Education in other Primary Schools. The results showed that Citizenship Education in Primary Schools has contributed in every effort to instill national character (nationalism) through several schemes: 1) Planning to instill national character (nationalism) by incorporating the value of national character (nationalism) into the Syllabus, thematic RPP , and Citizenship Education teaching materials in Elementary Schools; 2) How to assess the inculcation of national character (nationalism) through Citizenship Education in Primary Schools by assessing the cognitive domain through tests, affective domains through teacher observation sheets and coordination with religious and sports teachers, and psychomotor domains through the process and results of the assessment; 3) The strategy of instilling national character (nationalism) through Citizenship Education in Primary Schools is through comprehensive discussions and methods.